Quasi-Solid Polymer Electrolyte Composed of poly(1-vinylpyrrolidone-co-vinyl acetate) Copolymer and the Influence of Its Composition on Electrochemical Properties and the Performances of Dye-Sensitized Solar Cells - Ng, H.M.; Ramesh, Subramaniam; Ramesh, Kasi (Taylor & Francis, 2018)
Poly(1-vinylpyrrolidone-co-vinyl acetate)-based quasi-solid polymer electrolytes doped with potassium iodide are prepared. The highest room temperature ionic conductivity of 1.72 mS cm−1 is obtained. The dielectric studies are performed to understand the ion conduction mechanism. Fourier transform infrared study has been performed to understand complexation of the poly(1-vinylpyrrolidone-co-vinyl acetate)-based quasi-solid polymer electrolytes. The best power energy conversion efficiency (η) obtained is 2.94% with short circuit current density (Jsc) of 8.05 mA cm−2, open circuit voltage (Voc) of 0.58 V, and fill factor of 63% under standard light intensity of 100 mW cm−2 irradiation.